DAMPAK DANA DESA DALAM PEMBANGUNAN DESA ( Studi Di Desa Tunjungtirto Kecamatan Singosari Malang) - Fatah, Zainal (ASKETIK, 2018)
The Village Fund is a fund sourced from the State Revenue and Expenditure Budget that is designated for the Village that is transferred through Budget 21 of the District / City Expenditure and is used to finance the administration, and the empowerment of the community. (Law Number 6 Year 2014 Article 1 About the Village). The Village Fund is managed in an orderly manner, obedient to the provisions of legislation, efficient, economical, effective, transparent and accountable with due regard to the sense of justice and compliance and prioritizing the interests of the community. With the Village Fund, the village government is required to manage the village funds effectively and accountably. effective is the extent to which the target (quantity, quality and time) has been achieved by the village government in the utilization of village funds. This research is conducted to give an illustration of the extent of the impact of village funds in village development in Tunjungtirto Village Singosari Subdistrict and whether the village funds are used according to the program. The impact analysis focuses on the areas of development which includs the construction of basic facilities and infrastructure, the construction of basic social service facilities and infrastructure, the construction of economic facilities and infrastructure. Based on the program of the implementation of village funding during the last three years from 2015 to 2017, it can be explained that the impact of village funds on the development of Tunjungtirto village are: First, in the field of basic infrastructure facilities, an improvement of residential environment and transportation in the area Tunjungtirto has been made because a number of programs have been carried out for the development of physical facilities and infrastructure such as the construction and improvement of existing water drainage in the neighborhoods of each RT in the Tunjung Tirto Village area, the environmental supporting facilities of the Garbage Disposal Site (TPS). 2. Secondly in the field of social services infrastructure, has had a very good impact on the education needs of children and health of residents in the village Tunjungtirto with the program development activities and repairs of school buildings early childhood, Taman Pendidikan Alquran (TPQ), health posts in some RT and RW in the village Tunjungtirto. 3. The three impacts of the economic infrastructure, by providing facilities by building a community economic facility (Sareko) on the Karangploso highway to provide an ease of place to sell various results of economic activities based on the household. The conclusions of the research results are: 1. Village Fund Implementation in Tunjungtirto Village has been implemented for development activity program in accordance with development priority set by Permendes PDTT, 2. Determination of Program of development activity funded by Village Fund is done through participative process (buttom up) , transparent and accountable by implementing Deliberation of Village Development Plan (Musrenbangdes). 3. The Impact of Village Funds in the development of village development areas covering basic infrastructure, basic social service facilities, and economic infrastructure have a positive impact for the village community. 4. The impact of village funds on community empowerment is useful in mobilizing household-based economic activities in management, production and distribution. 5. Impact of Village Funds for Village Governments can give acceleration of village development in order to achieve the vision and mission of Tunjungtirto village government in RPJMDes.